Posisi Indonesia Dalam Rezim UNESCO Perlindungan Cagar Budaya Bawah Air: Pencurian Bangkai Kapal Milik Asing di Laut Indonesia - Ridlo, Muhammad Mu’adz Hafidz; Alfian, Muhammad Faizal (Journal of International Relations, 2021)
The theft of foreign shipwrecks that have sunk in Indonesian seas is one of the major cases of theft of underwater cultural heritage that occurs in the world. Apart from that, ship nations such as Australia, the Netherlands, England, and even the United States also expressed their disappointment with Indonesia, which was deemed incapable of protecting the legacy of their ancestors which was also considered as an underwater cultural heritage object. In this research, the researcher tries to examine the position and capability of Indonesia in the aspects of maritime security, both politically and domestically militarily. The author uses an analytic-qualitative method by comparing journals and case reports of shipwreck theft as the main method of this research. Using the theory of institutionalism, the author tries to explain Indonesia's position in international regimes such as UNESCO 1970 and 2001 for the protection of underwater cultural heritage as well as the concept of rational choice or rational choice to dissect Indonesia's reasons for taking this position. Using these methods and theories, the authors know that Indonesia does not want to ratify the UNESCO 1970 and 2001 regime due to domestic considerations, considerations of capability and sovereignty.